Experimental phosphate limitation in Nodularia spumigena CCY9414 - Mariano Santoro; Christiane Hassenrück; Matthias Labrenz; Martin Hagemann (PANGAEA, 2022)
Nodularia spumigena is a toxic, filamentous cyanobacterium capable to fix atmospheric nitrogen, which is often dominating cyanobacterial bloom events in the Baltic Sea and other aquatic systems worldwide. Phosphate (P) limitation has been considered as one environmental parameter that is somehow promoting the establishment of cyanobacterial mass developments. In the present study, we analyzed the response of Nodularia spumigena strain CCY9914 towards strong phosphorus limitation in an experimental approach. Pre-experimental and experimental incubations were performed at the Department of Plant Physiology (University of Rostock, Germany). Specifically, cultures were incubated under P-replete and P-deplete conditions for 21 days. The P-replete medium was composed as follows: 33% ASNIII and 67% BG11 medium mixture (as described by Hagemann et al., 2019), with 0.02 g L-1 K2HPO4 in the modified ASNIII (Rippka et al., 1979) and 0.00078 mg L-1 K2HPO4 in BG11 medium modified with 20 mM TES buffer to pH 8 (Rippka et al., 1979). Conversely, the P-deplete medium did not contain any additional P. Samples were collected after 3 hours (day 0), 7, 14 and 21 days from the start of the experiment to assess the variation of the following physiological parameters: biomass increase estimated by dry weight measurements and polyphosphate accumulation measured according to Martin et al. (2014). Additionally, ortho-phosphate and ammonium concentrations were measured in the medium to assess nutrient conditions during the course of the experiment. The experiment was repeated two times. During the second iteration of the experiment, samples from d7 and d14 were used for differential gene expression analysis (RNA-seq data available on Gene Expression Omnibus (GEO) accession GSE213384).